Identification of an Alkylhydroquinone from Rhus succedanea as an Inhibitor of Tyrosinase and Melanogenesis - Chen, Yun-Ru; Chiou, Robin Y.-Y; Lin, Ting-Yu; Huang, Cheng-Po; Tang, Wei-Chien; Chen, Shui-Tein; Lin, Shwu-Bin (Journal of agricultural and food chemistry, 2009)
The alkylhydroquinone 10′(Z)-heptadecenylhydroquinone [HQ17(1)], isolated from the sap of the lacquer tree Rhus succedanea, was found to inhibit the activity of tyrosinase and to suppress melanin production in animal cells. The IC50 of HQ17(1) as a tyrosinase inhibitor was 37 μM versus 70 μM for hydroquinone (HQ), a known inhibitor of tyrosinase and melanogenesis. For the inhibition of melanin production in mouse B16 melanoma cells, the EC50 of HQ17(1) was 40 μM versus 124 μM for HQ. HQ17(1) induced much less oxidative stress than did HQ. The effectiveness in inhibiting melanin production could be mimicked by intermittent exposure of cells to HQ17(1). The potent inhibitory effects of HQ17(1) on tyrosinase activity and melanin production are likely due to its heptadecenyl chain, which facilitates retention of the compound in cell membrane compartments and may impede oxidation of the hydroquinone ring. As tyrosinase activity accounts for postharvest browning of botanical products and animal skin melanogenesis, HQ17(1) could be useful for the preservation of these products or as a skin-whitening cosmetic.